Childhood Maltreatment and Physical Health in College Students: Physical Activity and Binge Eating as Moderators - Moore, Susannah M. (Journal of interpersonal violence, 2025)
Child maltreatment leads to pervasive physical health problems. For individuals with a child maltreatment history, physiological risk factors for future disease are apparent by young adulthood. The current study explored the role that physical activity and binge eating may have in the trajectory from child maltreatment to poor adult health. We administered the following measures to 100 female and male college students: resting heart rate assessment, symptoms of illness, and the Childhood Trauma Questionnaire (CTQ-SF) to assess maltreatment history. After this session, participants wore a Fitbit that provided physical activity data (low, moderate, and vigorous activity, and total steps) in a free-living environment for a period of 10 days. Physical activity moderated the pathway between maltreatment history and both resting heart rate and symptoms of illness. In individuals with higher CTQ scores, more low-intensity physical activity and total steps were related to fewer symptoms of illness and lower resting heart rate, respectively. Binge-eating behavior moderated the pathway between maltreatment and symptoms of illness, such that greater binge-eating behavior was associated with more self-reported illness symptoms in participants with higher CTQ scores. These findings suggest that on-campus interventions targeting physical activity and healthy eating behaviors will improve the long-term health of young adults with maltreatment history.